Portable beverage cooler using the thermoelectric and microcontroller - saharuddin, sahar; Habibullah (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Design and Build Portable Beverage Coolers Using Tec1-12706 Modules and Microcontrollers aims to design and build a beverage cooling system using the TEC1-12706 pitier thermoelectric module based on the arduino uno microcontroller so that it becomes one of the alternatives in the application of environmentally friendly cooling systems and testing the device. Peltier's cooling ability is affected by the cooling process on the heat side emitted by Peltier, because if the heat is not absorbed or cooled, Peltier's performance will not be optimal. Peltier testing was carried out in an open room for 4 minutes with an ambient temperature of 29oC, the test results on the cold side of Peltier were obtained a maximum temperature of -4.9oC, while Peltier testing on the hot side obtained a maximum temperature of 32.2oC. Peltier was able to reach a low temperature of -4.9°C in 2 minutes and 20 seconds but rose again to -4.2°C after 4 minutes of running. To cool 1 bottle of mineral water (300 ml) for 30 minutes can produce a temperature of 18.69oC. To cool 2 bottles of mineral water (600 ml) with the same time, namely 30 minutes, can produce a temperature of 22.31oC. And to cool 3 bottles of mineral water (900 ml) with the same time, namely 30 minutes, it can produce a temperature of 25.06oC. More and more drink objects will be added